1982
DOI: 10.1042/bj2040361
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-hydrolysing enzymes in blowfly salivary glands

Abstract: The salivary glands of adult blowflies (Calliphora erythrocephala) contain enzymes that hydrolyse phosphatidylinositol, predominantly by a Ca2+-independent deacylation, though a Ca2+-dependent phosphodiesterase (phospholipase C) activity could be detected. The deacylating enzymes could also hydrolyse phosphatidylcholine and phosphatidylethanolamine, and were secreted in the saliva. Homogenization of salivary glands prelabelled with [3H]inositol resulted in a rapid deacylation of the endogenous 3H-labelled phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Ins(l,4,5)P3-3-kinase activity is also localised primarily in the cytosolic fractions of bovine brain [54] and rat liver [551 and guinea pig peritoneal macrophages [56]. The apparent K, (0.42 pM) of the purified muscle Ins(1,4,5)P3 3-kinase for Ins (1,4,5)P3 is similar to that reported in other tissues (0.21-0.70 pM) [54,[57][58][59][60]. The conversion of Ins( 1,4,5)P, to Ins( 1 ,3,4,5)P4 may be a secondary pathway for Ins(1,4,5)P3 metabolism, with the main function of Ins( 1,4,5)P, 3-kinase being to regulate the relationship between 1ns(1,4,5)P3 and Ins(1,3,4,5)P4, whose roles in Ca2+ signalling may be closely associated [61].…”
Section: Kinetics Of Ins( 145)p3 and Ins(1345)p4 Metabolismsupporting
confidence: 72%
“…Ins(l,4,5)P3-3-kinase activity is also localised primarily in the cytosolic fractions of bovine brain [54] and rat liver [551 and guinea pig peritoneal macrophages [56]. The apparent K, (0.42 pM) of the purified muscle Ins(1,4,5)P3 3-kinase for Ins (1,4,5)P3 is similar to that reported in other tissues (0.21-0.70 pM) [54,[57][58][59][60]. The conversion of Ins( 1,4,5)P, to Ins( 1 ,3,4,5)P4 may be a secondary pathway for Ins(1,4,5)P3 metabolism, with the main function of Ins( 1,4,5)P, 3-kinase being to regulate the relationship between 1ns(1,4,5)P3 and Ins(1,3,4,5)P4, whose roles in Ca2+ signalling may be closely associated [61].…”
Section: Kinetics Of Ins( 145)p3 and Ins(1345)p4 Metabolismsupporting
confidence: 72%
“…The ability of this PLB to hydrolyse PE is probably a major reason why expression of this protein in E. coli is compromised. It has also been previously reported that the salivary glands of adult blowflies (Calliphora erythrocephala) contain enzymes that deacylate PI, PC and PE, and were secreted in the saliva [40]. The presence of a signal sequence together with the knowledge that a …”
Section: Discussionmentioning
confidence: 99%
“…These iso-enzymes have different substrate specificity with respect to Ins(l,4,5)P3 and lns(1 ,3,4,5)P4. The kinase that phosphorylates Ins(1,4,5)P3 at the 3-position is present in a soluble form in virtually all mammalian cells [229,258,2591 and is activated in most if not all tissues by Ca2+/calmodulin [260,261]. Moreover, Ins(1 ,4,5)P3 3-kinase and 5-phosphatase activities may be stimulated by agents that activate protein kinases A and C, respectively [262,2631.…”
Section: Adenylate Cyclase Pathwaymentioning
confidence: 99%